The efficacy and safety of tadalafil in the management of erectile dysfunction with diabetes and blood circulation issues - Jong Seung Lee; Seung-ho Hong; Hwa Yeon Sun; Hyunseung Jin; Byung Yeon Yu; Yong-jin Cho; Jin young Chang; Byung Wook Yoo (The Aging Male, 2023)
AbstractBackground Erectile dysfunction (ED) is a common diabetes-related complication.Materials and methods This study examined the effect of daily low-dose tadalafil (5 mg) on patients’ quality of life (including that of sex life) and blood circulation. Erectile dysfunction questionnaires were administered to 20 patients with type 2 diabetes (T2DM) and ED. The safety and efficacy of tadalafil were evaluated using laboratory tests, and the effect on blood circulation was measured through nail fold capillaroscopy.Results Daily tadalafil use by patients with T2DM and ED showed a statistically significant increase in the erectile reliability score from of 1.15 to 3.20 (p < .00012). Capillary blood circulation improvement tests showed a statistically significant increase in apical limb width from 13.1 to 14.64 µm (p = .04829) and flow from 9035 to 11946 μm3/s (p = .04405). Although not significant, increased capillary width and speed (rate of blood flow) confirmed improved blood circulation. There were no significant changes in the cardiac indicators (troponin, prostate-specific antigen, or electrocardiogram tests) before and after tadalafil administration, supporting the safety of its low-dose daily administration.Conclusions A small dose of daily tadalafil was shown to safely improve erectile dysfunction and peripheral blood flow in patients with T2DM, in which peripheral arterial diseases should not be considered separately but rather as complex entities.